The importance of bentonite clays in the cultivation of agricultural crops (Texas Journal of Agriculture and Biological Sciences, 2024)
The article highlights the use of bentonite clays, which are one of the non-traditional agricultural ores, as fertilizers and obtaining high and high-quality crop yields, as well as a positive effect on changing the mechanical composition of the soil, which is one of the important factors in increasing soil fertility.